Halal Industry as a Reinforcement of Indonesia’s Economic Growth through the Export Market - Ardiansyah, Muhammad Rajab; Lubis, Fauzi Arif; Bi Rahmani, Nur Ahmadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to analyze the influence of the Halal Industry on Indonesia’s Economic Growth and Export Markets as Intervening Variables. This research uses a quantitative approach with a verification type of research. Secondary data was obtained through the Statistics Center (BPS), namely data on halal products, exports, and economic growth. The population in this research is the overall growth data for each variable from 2015 to 2021. The samples used in this study were Halal Products and Exports during the 2015-2021 period, each of which consisted of 84 samples taken from annual data in the form of time series data using data interpolation. Other data was obtained through observation and literature study. The analysis technique used is multiple linear regression. The results of the study show that Halal Food, Halal Fashion, and Halal Cosmetics have an effect on Economic Growth in Indonesia and Export Markets as Intervening Variables in the high category.